The history of the great migration: Movement to the urban north (1916-1970) and its cultural, social, and political impact - Jadallah Khasawneh, Asma (Edelweiss Applied Science and Technology, 2024)
The main purpose of the article is to conduct a historical analysis of the extensive migration that took place during 1916-1970. The object of the study is the cultural, social and political effect of this phenomenon. The methodology of the study involves the use of historical analysis methods, methods of systematization of available historical information, the method of expert analysis, the method of hierarchical analysis and the method of pair comparison. As a result of the study, key cultural, social and political factors that influenced the process of formation of large migration in the period 1916-1970 were identified through the conducted expert historians. A model of the hierarchical influence of these factors on the formation and development of migration processes is presented. The study has a limitation and takes into account only a specific period in history. At the same time, in further studies, a significant scientific emphasis should be placed on economic factors.